Māori Policy and Politics - Sullivan, Ann (New Zealand government & politics, 2006)
Keywords: Elections – New Zealand; New Zealand – Politics and government – 1972-; New Zealand Parliament – Elections; 2005; Political parties – New Zealand; Proportional representation – New Zealand; Representative government and representation – New Zealand

Māori Party - Smith, Kaapua (New Zealand government & politics, 2006)
Keywords: Elections – New Zealand; New Zealand – Politics and government – 1972-; New Zealand Parliament – Elections; 2005; Political parties – New Zealand; Proportional representation – New Zealand; Representative government and representation – New Zealand

The rights of indigenous peoples - Charters, Claire (New Zealand Law Journal, 2006)
Keywords: UNDRIP; māori rights; self-determination; tino rangatiratanga

Changing the game plan: The Foreshore and Seabed Act and constitutional change - Bargh, Maria (Kōtuitui: New Zealand Journal of Social Sciences Online, 2006)
The Foreshore and Seabed Act 2004 caused many New Zealanders grave concern. In this article I suggest that a number of the Government's actions since the passing of the Foreshore and Seabed Act bring into question several of its central claims for legislating and the subsequent overriding of Tiriti o Waitangi and human rights laws. As a result, I argue that the inadequacy in our constitutional arrangements requires a change of approach—a new game plan: constitutional change. The second part of the article examines the work of the Maori Party. Its actions in encouraging an increasing level of Maori politicisation away from expression outside the State and towards the electoral process, arising out of opposition to the Foreshore and Seabed Act, constitute another changing of game plans. The article concludes by emphasising how the Foreshore and Seabed Act has encouraged us to take a longer term vision in order to foster more positive relations, a vision that encompasses the need for genuine constitutional change based on respect for human rights and Te Tiriti o Waitangi.
Keywords: constitutional transformation; crown policy; foreshore and seabed act 2004; institutional racism; kāwanatanga; political activity; te pāti māori; treaty obligations

The foreshore and seabed what now for Maori and the Government? - Bargh, Maria (Macmillan Brown Centre for Pacific Studies, University of Canterbury, 2006)
Keywords: government relations; kaitiakitanga; kāwanatanga; land tenure; law; legislation; new zealand foreshore and seabed act 2004; seashore; takutai moana; tikanga | indigenous law; tino rangatiratanga; ture whenua

Needs, rights, nationhood, and the politics of indigeneity - O’Sullivan, Dominic (MAI review, 2006)
In 2004 the appointment of a Coordinating Minister Race Relations, signalled a shift in elite Māori policy thinking from a long-standing cautious bipartisan acceptance of selfdetermination towards a re-emergent assimilationist ‘one law’ for all discourse. The question simplistically posed by the Leader of the Opposition was should welfare entitlements be granted on the basis of need or race (Brash 2004)? Beneath this question lies an ideological assumption which privileges assimilation over indigeneity as the basis of Māori participation in public affairs. This paper therefore asks: are Māori peoples with rights, or individuals with needs? Is there a deeper politics of indigeneity providing a legitimate foundation for rights which are not necessarily superior to the rights of citizenship, but are important and distinguishable adjuncts? These questions transcend the issue of welfare entitlements to wider questions about the nature and terms of Māori belonging to the liberal polity. The paper highlights the political tension between government attempts to remove indigeneity from the public agenda in response to populist pressure and a pragmatic acceptance that New Zealand ‘needs’ Māori to increase their contribution to the national economy and that the realisation of this goal may in fact depend on the fuller citizenship imagined by the politics of indigeneity.
Keywords: assimilation; indigenous rights; māori rights; rangatiratanga; self-determination

Kei a koe te tikanga - it's your choice; The history of the Māori seats - Mulholland, Malcolm (Karaka (Christchurch, N.Z.), 2006)
Notes that the five-yearly Maori Electoral Option, during which Maori voters may chose to be on either the general or Maori electoral rolls, runs f...
Keywords: elections; government; māori electorates; māori seats

Globalisation, neo-liberalism and the struggle for indigenous citizenship - MacDonald, Lindsey Te Ata o Tu; Muldoon, Paul (Australian Journal of Political Science, 2006)
Using indigenous citizenship as a frame, the article examines the deeply ambiguous effects of globalisation for indigenous peoples in the Antipodes. We demonstrate that processes of economic globalisation have had an impact upon New Zealand Maori and Australian Aboriginals in ways that have heightened their vulnerability and undermined their citizenship entitlements. However, we also argue that Maori and Aboriginal peoples have used the reforms of state practice brought about by globalisation to gain greater control over their existence.

Cultural Well-being and Local Government: Lessons from New Zealand - Dalziel, Paul; Matunga, Hirini; Saunders, Caroline (The Australasian Journal of Regional Studies, 2006)
Reforms of local government legislation in the United Kingdom (2000) and in New Zealand (2002) both introduced well-being powers. The UK reform gave local government a new power to promote social, economic and environmental well-being, but New Zealand added a fourth dimension - cultural well-being. This paper examines the background to New Zealand's 'quadruple bottom line' approach. It explains that it was the result of policymakers in New Zealand grappling for 25 years with the question of how to give effect to what the Town and Country Planning Act 1977 described as 'the relationship of the Maori people and their culture and traditions with their ancestral lands'. New Zealand's legislation requires a fully integrated approach by decision-makers using the well-being power, and the essay concludes with a discussion of how this has provided a forum for contests and compromises over cultural well-being to take place within a framework of democratic local decision-making by communities.
Keywords: assimilation; government relations; local government; sustainable development